Effectiveness of the Utilized Interview Techniques to Enhance Speaking Skills of Students - Beruela , April Jenica B.; Bobier, Mayianne Rose E.; Caceres, Aileen V.; Cortez, Joyce Ann P.; Ciudadano, Mary Camille E.; Santos , Kiezzel Grace D. Delos; Durante , Mary Ann A.; Prima , Cleotilde A. (Educalingua Journal, 2023)
Speaking is regarded as one of the most difficult aspects of language learning because learners find it difficult to express themselves and are affected by factors that led them to be reluctant to speak. Hence, this study 1. determined the factors affecting the skills of the students in speaking English. 2. Documented the utilization of the interview techniques to enhance the speaking skills of the students and discussed the challenges encountered and 3. Analyzed the perceived effectiveness of the utilized interview techniques to enhance the students' speaking confidence. The study used a mixed-methods approach using pre- and post-surveys, interviews, and group discussions. The respondents were the 22 Grade 10-Abad students of Tinago National High School. Results showed that students struggle to speak English because of the following factors: pronunciation, vocabulary, fear of public speaking, criticism, and shyness. Using criteria as an assessment tool, it revealed that there was an improvement of 20% in the students’ English-speaking skills when the interview techniques of PREP and STAR methods were used as an activity, concluding that the usage of utilized interview techniques enhanced the English-speaking skills of students.